Acute cutaneous zygomycosis of the scalp: A case report and literature review - Abdulrahman Alseady; Salim Baharoon (Elsevier, 2015)
Summary: Cutaneous zygomycosis is the third most common form of zygomycosis. However, scalp involvement is rare for this disease. In this study, we present a case of acute zygomycosis in a diabetic patient who was effectively treated with local debridement, amphotericin B lipid complex and posaconazole. Keywords: Cutaneous zygomycosis, Zygomycosis, Scalp